PENERAPAN MEDIA PEMBELAJARAN WORDWALL QUIZ DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN PENGELOLAAN BISNIS RITEL KELAS XI BD DI SMK NEGERI 1 JOMBANG - Alfina Febianti, Alfina Febianti; Finisica Dwijayati Patrikha (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to analyze the application of Wordwall Quiz learning media and learning styles to the learning outcomes of grade XI BD students at SMK Negeri 1 Jombang. This type of research is an experimental research. The research design used is a pretest-posttest control group design. The sample in the study was 72 students using the purposive sampling technique. Class XI BD 2 is used as a learning control class using conventional media. Meanwhile, class XI BD 3 is used as an experimental class for learning using Wordwall Quiz media. Data collection uses questionnaires and learning outcome tests. The results showed that there were differences in the learning outcomes of students in the experimental class before and after using the wordwall quiz based on auditory and visual learning styles, there were differences in learning outcomes between the experimental class and the auditory learning style control, and there were differences in learning outcomes between the experimental class and the visual learning style control class. Based on the analysis that has been carried out, it can be concluded that there is a difference in the learning outcomes of the experimental class and the control class based on their learning style.